2013
DOI: 10.1536/ihj.54.123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Myocardial Infarction in Young Japanese Patients

Abstract: SummaryClinical features and outcomes of acute myocardial infarction (AMI) in the young have been poorly investigated. The aim of this study was to investigate the clinical features and hospital outcomes of AMI in young Japanese. We conducted a case-control study. A total of 53 consecutive AMI patients whose age was ≤ 45 years old were assigned to the young group and 106 AMI patients whose age was > 45 years old were assigned to the non-young group. We compared the clinical features and hospital outcomes betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Previous studies have demonstrated that the young AMI group has a higher proportion of males, presenting with modifiable risk factors such as smoking, hyperlipidaemia, and being more overweight with respect to the older age group 15 16. Similar to Western data, we found that young men have more AMI than women of the same age group 17 18.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have demonstrated that the young AMI group has a higher proportion of males, presenting with modifiable risk factors such as smoking, hyperlipidaemia, and being more overweight with respect to the older age group 15 16. Similar to Western data, we found that young men have more AMI than women of the same age group 17 18.…”
Section: Discussionsupporting
confidence: 86%
“…In some prior studies, the association between triglycerides and CAD became statistically insignificant after adjusting for HDL cholesterol and other cardiovascular risk factors (24,25). older patients tend to have multi-vessel disease (2)(3)(4)(5)(6). The same studies also demonstrated that young patients have shorter length of hospital stay and lower morbidity and mortality when…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Traditional comorbid conditions, however, including hypertension, diabetes mellitus and previously established coronary artery disease (CAD), are less prevalent in this patient population (1, 2,[4][5]. Previous studies have also demonstrated a higher likelihood of single vessel CAD (2)(3)(4)(5)(6) and lower rates of in-hospital morbidity and mortality when young patients with AMI are compared with older patients (1-6).…”
Section: Introductionmentioning
confidence: 94%
“…Myocardial infarction risk profiles also differ for younger adults. Smoking and hyperlipidaemia are higher, while hypertension and diabetes rates are lower, and the majority of MI patients under 45 are male (Al‐Murayeh, Al‐Masswary, Dardir, Moselhy, & Youssef, ; Anderson et al ., ; Jinnouchi et al ., ; Khan, Khan, Khan, Shah, & ul Hassan, ; Morillas et al ., ; Zimmerman, Cameron, Fisher, & Grace, ). Although this gender imbalance is not fully understood, it has been suggested that oestrogen protects younger women from atherosclerosis (Maxwell, ), while lifestyle factors such as smoking and drinking predispose men to MI (Solomon, ).…”
Section: Introductionmentioning
confidence: 99%